ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI SUHU DAN KALOR (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
In learning, the ability to think critically must be trained and familiarized. The goal is for learners to understand the concepts of science and not just remember formulas. Critical thinking is the ability to think with high curiosity about information to gain insights. The method used in this study is a qualitative descriptive method that aims to describe the critical thinking ability of students. the results showed that the critical thinking ability of students is still low, so they still have to be trained and familiarized. To help improve students' critical thinking skills, they can use the right learning models and learning methods.Keywords : critical thinking ability, learning model, learning method